E.01 Lost productivity in stroke survivors: a new econometrics model. (17th June 2016) - Vyas, MV; Hackam, DG; Silver, FL; Laporte, A; Kapral, MK
Abstract : Background: Stroke leads to a substantial societal economic burden. We aimed to characterize productivity and factors associated with employability in Canadian stroke survivors.Methods: We used the Canadian Community Health Survey (CCHS) 2010-2011 to identify stroke survivors and employment status. We used multivariable models to determine the impact of stroke on employment and factors associated with employability. We used the Heckman model to estimate the effect of stroke on productivity (number of hours worked/week and hourly wages).Results: We included data from 91, 633 respondents between 18 and 70 years and identified 923 (1%) stroke survivors. Stroke survivors were less likely to be employed (adjusted Odds Ratio 0.39, 95% CI 0.33 to 0.46) and had hourly wages 17.7% (95% CI 8.3% to 27.1%) lower compared to the general population, although there was no association between work hours and being a stroke survivor. Older age, being single and having medical comorbidities were associated with lower odds of employment in stroke survivors.Conclusions: Stroke survivors are less likely to be employed and earn a lower hourly wage than the general population. Interventions such as dedicated vocational rehabilitation and policies around return to work could be considered to address this lost productivity among stroke survivors.